Comparison of selected chemical properties of peat swamp soil before and after timber harvesting - Salimin, Muhamad Ismawi; Gandaseca, Seca; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2010)
Problem statement: Peat swamp is an important component of the world’s wetlands. Once they are disturbed the tendency for the soil degradation is very high. This study compared selected chemical properties of a peat swamp soil before and after timber harvesting. Approach: Peat soil samples were taken at 0-15 cm depth in 6 plots with 0.1 ha each plot at Batang Igan forest at Sibu Sarawak, Malaysia. The soil samples were analyzed for selected soil chemical properties. Data were analyzed by using Statistical Analysis System (SAS) version 9.2. Results: The tropical peat swamp forest indicate its specific natural state such as rich in soil pH KCl and except for C/N ratio, the selected chemical properties such as soil pH water, cation exchange capacity, soil organic matter, total carbon, total nitrogen, total phosphorus and exchangeable potassium were significantly different between before and after timber harvesting. Conclusion: Timber harvesting has significant effect on chemical properties of peat swamp.